An Examination of Churn Within Australian Family Services: A Scoping Study. Issue 2 (3rd April 2023) - Hatzikiriakidis, Kostas; Skouteris, Helen; Vicary, Dave; Fittock, Noel; Hogan, Candas; Diamond, Susan; Demeyer, Chris; Stopczynski, Jurek; O'Donnell, Renée
ABSTRACT: Churn, the persistent cycling of families in and out of family service programs without sustainable change, places an extremely high burden on families and the broader family services system. Yet, only a handful of studies based in the United States have examined the process of churn. As churn is a novel field of enquiry, this study aimed to generate consensus among key stakeholders who work within the Australian family services sector regarding the definition, implications, and predictors of churn, which will subsequently inform future research and intervention development to mitigate the incidence of churn. Stakeholders were engaged through an initial participatory research workshop, followed by a two-round Delphi study. The findings provided compelling insights into the nature of churn within the context of Australian family services and highlight the importance of substantial systemic change in order to mitigate and address the incidence of churn. IMPLICATIONS The results of this study have provided compelling insights into the process of churn, the client and service-level factors that contribute to it, and the impact it has on families, staff, and the broader family services system. Stakeholders provided several recommendations to inform the development of future interventions that will be applied within the Australian family services system in order to identify and address the specific needs of families.